Impacts of Climate Change on Oral Health and Dentistry - Why Should Dentists Care and What Can They Do? - Nancy Hu (Journal of the California Dental Association)
Background Anthropogenic climate change is recognized as one of the most significant global health threats, with profound implications for public health, including oral health. This paper explores the complex relationship between climate change and its impact on oral diseases and the delivery of oral health care. The environmental footprint of oral health practices underscores the need for sustainable approaches within the field.Methods Methods included searching Pubmed and Google Scholar from 2014 to 2024 for articles and government reports in English pertaining the impacts of climate change on human health, with considerations to how each aspect influences oral health. Books, articles, and content from courses on sustainability in dentistry were also reviewed.Results Shifting environmental conditions may increase the risk of oral diseases through disruptions in food security, air and water quality, and extreme weather events, while also challenging the infrastructure of dental care systems.Practice Implications This paper outlines actionable strategies for integrating sustainability into dental practice. As oral health care providers, we occupy a critical role in promoting sustainability by educating patients, collaborating with colleagues, advocating for environmentally conscious policies, and leading change toward a more sustainable future in healthcare.